Call me irresistible - Phillips, Susan Elizabeth (New York : William Morrow, 2011)
Ostracized for her role in halting best friend Lucy's wedding, Meg finds herself stranded without family support in a hostile Texas town where she unexpectedly falls for Ted Beaudine.
Ted ("little Teddy" AKA "young Teddy" from Phillips's books Fancy Pants and Lady Be Good) is all grown up now, along with Lucy (from First Lady) and Meg (from What I Did For Love).
Keywords: Female friendship -- Fiction; Texas -- Fiction; Love stories